2014
DOI: 10.1111/jvim.12393
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia in Brachycephalic Dogs

Abstract: BackgroundBrachycephalic dogs are at risk for arterial hypertension and obstructive sleep apnea, which are both associated with chronic magnesium (Mg) depletion.Hypothesis/ObjectivesTo compare the period prevalence of hypomagnesemia between Boxers and Bulldogs presented to a referral teaching hospital. To screen a group of Bulldogs for evidence of hypomagnesemia, and to obtain pilot data regarding the utility of parenteral Mg tolerance testing (PMgTT) in the diagnosis of whole‐body Mg deficiency.AnimalsChemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Large studies on gastrointestinal disorders in healthy brachycephalic dogs are needed. Hypomagnesemia and hypercoagulation were found in clinically healthy bulldogs compared to nonbrachycephalic control dogs and boxers . Hypertension also was reported in systemically healthy pugs, Boston terrier, French bulldogs, and bulldogs .…”
Section: Discussionmentioning
confidence: 83%
“…Large studies on gastrointestinal disorders in healthy brachycephalic dogs are needed. Hypomagnesemia and hypercoagulation were found in clinically healthy bulldogs compared to nonbrachycephalic control dogs and boxers . Hypertension also was reported in systemically healthy pugs, Boston terrier, French bulldogs, and bulldogs .…”
Section: Discussionmentioning
confidence: 83%
“…In humans, hypomagnesaemia is associated with cardiac disease including hypertension (Fox et al . , Mellema & Hoareau ) and, although less clear, it may be linked to OSA (Blasco et al . ).…”
Section: Pre‐existing Conditions That Influence Anaesthetic Managementmentioning
confidence: 99%
“…). In one study, hypomagnesaemia was identified in 15% of Bulldogs (Mellema & Hoareau ); its clinical implications are unclear.…”
Section: Pre‐existing Conditions That Influence Anaesthetic Managementmentioning
confidence: 99%
See 2 more Smart Citations